Kepuasan Kerja Pada Karyawan PT. Ira Jaya Satria - Kamara, Jihan Heriani; Faadhil, Faadhil (Tabularasa: Jurnal Ilmiah Magister Psikologi, 2025)
This study aims to find out Job Satifaction Of PT. Ira Jaya Satria Employees. In this study, the sample used was 68 employees using the total sampling technique. Based on the analysis used in this study, Product Moment Correlation, data collection techniques using questionnaires and documentation. The data analysis technique uses a descriptive analysis technique which is then percentaged and categorized. The results of the study showed that employee job satisfaction was in the high category with a percentage obtained of 11.8% or as many as 8 employees stated that employee job satisfaction was very high, as much as 75.0% or as many as 51 employees stated that employee job satisfaction was moderate, by 13.2% or as many as 9 employees stated that employee job satisfaction was low Job satisfaction is reviewed from salary, promotion, employer, benefits, awards, work procedures, colleagues, nature of work and communication.